Exploring Task-Switching In Indonesia's Multilingual Context - Alifa Runi Larasati; Farah Mutiasari Djalal (Journal Research of Social Science, Economics, and Management, 2025)
The factors modulating the emergence of a bilingual advantage remain a topic of debate. While previous studies have adopted stark disparity of language experiences between language groups of interest, this study takes a different approach by examining bilingual and trilingual Indonesian participants, leveraging their unique characteristics of multilingual context. This study aims to test whether a less distinct difference in language experiences between groups affects task-switching performance. Data were collected using the task-switching paradigm and The Language Experience and Proficiency Questionnaire (LEAP-Q), while data analysis was conducted using two-way ANOVA. Results suggested no statistically significant difference in task-switching performance between the two groups. This study suggests the implications of cultural context in modulating these results, suggesting its significance following the shift into multilingual trends of executive control research.